ANALISIS PERBANDINGAN GROSS PROFIT MARGIN DAN NET PROFIT MARGIN PADA SUB SEKTOR ROKOK YANG TERDAFTAR DIBURSA EFEK INDONESIA - Aqidah, Fitratul; Munandar, Aris; Nurhayati (Scimadly Publishing, 2024)
This study aims to examine whether significant differences exist between the Gross Profit Margin (GPM) and Net Profit Margin (NPM) of companies in the cigarette subsector listed on the Indonesia Stock Exchange from 2013 to 2022. The research employs a comparative method to analyze these two profitability metrics, using ratio analysis and statistical tests. The GPM and NPM ratios were calculated, followed by normality tests and independent sample tests conducted with SPSS to determine whether variations between the two measures were statistically significant. The findings reveal no significant differences between GPM and NPM, as indicated by the results of both ratio analysis and statistical testing. This suggests that these profitability indicators exhibit consistent patterns within cigarette subsector companies during the observed period. The absence of significant variation between GPM and NPM highlights similar operational efficiency and cost management across the subsector, providing insights into the financial performance stability of cigarette companies in Indonesia over the decade analyzed.